2016
DOI: 10.1002/jmri.25509
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal carcinoma: Ex vivo evaluation by high‐spatial‐resolution T2‐mapping MRI compared with histopathological findings at 3.0T

Abstract: 1 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;45:1609-1616.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…On magnetic resonance imaging (MRI) routine nonenhanced T 1 ‐weighted imaging and T 2 ‐weighted imaging can be used to evaluate the esophageal wall invasion. But both of them fail to provide a prediction of histologic grade …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On magnetic resonance imaging (MRI) routine nonenhanced T 1 ‐weighted imaging and T 2 ‐weighted imaging can be used to evaluate the esophageal wall invasion. But both of them fail to provide a prediction of histologic grade …”
mentioning
confidence: 99%
“…But both of them fail to provide a prediction of histologic grade. [10][11][12][13][14][15] Diffusion-weighted imaging (DWI) is a noninvasive approach to probe molecular diffusion of water on the microscopic scale without contrast administration, 16,17 and the diffusion of water can be quantitatively described by the apparent diffusion coefficient (ADC). Recently, a few studies have demonstrated that DWI along with ADC measurement is helpful in detecting, characterizing, and staging malignant lesions.…”
mentioning
confidence: 99%
“…MRI allowed a correct T staging in 29/32 tumors (90.6%). The accuracy was 93.8%, 90.6%, 96.9%, and 100% for diagnosing an infiltration of the mucosa, submucosa, muscularis propria, and adventitia, respectively (32). Using a 4.5-T MRI, Yamada et al studied in a similar study setting 70 esophageal squamous cell carcinomas.…”
Section: A-mri For Esophageal Cancer Stagingmentioning
confidence: 99%
“…Water T 1 , and T 2 and fat content are important for tissue characterization in MRI. For example, T 1 , and T 2 values are altered in several diseased states, such as cardiac [1,2], liver [3], muscular [4], and others [5,6], in which the affected organs may contain or be near adipose tissue. The MRI-estimated fat signal fraction (FSF) is important in studies of healthy and pathological function, including brown adipose tissue [7] and abdominal organs [8][9][10].…”
Section: Introductionmentioning
confidence: 99%